Differences in leukocyte differentiation molecule abundances on domestic sheep (Ovis aries) and bighorn sheep (Ovis canadensis) neutrophils identified by flow cytometry. (June 2016) - Highland, Margaret A.; Schneider, David A.; White, Stephen N.; Madsen-Bouterse, Sally A.; Knowles, Donald P.; Davis, William C.
Highlights: Eosinophil autofluorescence allows cell-type specific gating of sheep granulocyte. Leukocyte composition is significantly different in domestic and bighorn sheep. Abundance of CD11a, CD11b, CD18, CD172a is greater on domestic sheep neutrophils. Abundance of CD14 is greater on bighorn sheep neutrophils. Abundance of CD25 is greater on bighorn sheep ConA stimulated lymphocytes. Abstract: Although both domestic sheep (DS) and bighorn sheep (BHS) are affected by similar respiratory bacterial pathogens, experimental and field data indicate BHS are more susceptible to pneumonia. Cross-reactive monoclonal antibodies (mAbs) for use in flow cytometry (FC) are valuable reagents for interspecies comparative immune system analyses. This study describes cross-reactive mAbs that recognize leukocyte differentiation molecules (LDMs) and major histocompatibility complex antigens on DS and BHS leukocytes. Characterization of multichannel eosinophil autofluorescence in this study permitted cell-type specific gating of granulocytes for evaluating LDMs, specifically on neutrophils, by single-label FC. Evaluation of relative abundances of LDMs by flow cytometry revealed greater CD11a, CD11b, CD18 (β2 integrins) and CD 172a (SIRPα) on DS neutrophils and greater CD14 (lipopolysaccharide receptor) on BHS neutrophils. Greater CD25 (IL-2) was identified on BHS lymphocytes following Concavalin A stimulation. While DS and BHS have similar total peripheral blood leukocyte counts, BHS have proportionately more neutrophils.